Contemporary Management Approaches for Spinal Subdural Hematoma in the Pediatric Population: Scoping Review - Farhad BALAFIF; Donny Wisnu WARDHANA; Tommy Alfandy NAZWAR; MUSTOFA (Modern Medicine)
This scoping review study describes the assessment of articles relevant to the management of spinal subdural hematoma in the pediatric population. The assessment of the articles was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Extension for Scoping Reviews guidelines. Of the 14 articles analyzed, the main focus was on management as well as evidence-based approaches in cases of pediatric spinal subdural hematoma. In the reviewed articles, various aspects related to intervention techniques, prevention strategies, and post-treatment follow-up were discussed. The findings of this review highlight the importance of a holistic and evidence-based approach in managing cases of spinal subdural hematoma in the pediatric population. The clinical implications of these findings may help improve medical understanding and practice in effectively managing this complex condition.